Digitalisasi Bagi Pelaku UMKM Yang Terdampak Pandemi Covid-19 - Erynayati, Luh; Dwika Ayu Amrita, Nyoman (Jurnal Etnik: Ekonomi-Teknik, 2022)
The Covid-19 pandemic had a negative impact on MSMEs, one of which was a decline in sales and asked MSMEs to rebuild their business systems to bear the impact of the pandemic. This procedure is a variation step as an option to become and turn into a superior Micro, Small and Medium Enterprises (MSMEs), especially during the Covid-19 pandemic. The strategy used in this research is subjective exploration, which is research based on the power of scientific description through a careful search of writings and descriptions through external and internal investigations of the problem. Composing with a subjective strategy can indicate a translation that is an item or a consistent result of the information obtained during the review. The results of the review explain that digital promotion of goods makes it easier for clients to get data about an item, and can create web-based exchanges so that they can increase sales transactions, especially for MSMEs.